3(2x-1)=4x-7

Simple and best practice solution for 3(2x-1)=4x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-1)=4x-7 equation:


Simplifying
3(2x + -1) = 4x + -7

Reorder the terms:
3(-1 + 2x) = 4x + -7
(-1 * 3 + 2x * 3) = 4x + -7
(-3 + 6x) = 4x + -7

Reorder the terms:
-3 + 6x = -7 + 4x

Solving
-3 + 6x = -7 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + 6x + -4x = -7 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-3 + 2x = -7 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + 2x = -7 + 0
-3 + 2x = -7

Add '3' to each side of the equation.
-3 + 3 + 2x = -7 + 3

Combine like terms: -3 + 3 = 0
0 + 2x = -7 + 3
2x = -7 + 3

Combine like terms: -7 + 3 = -4
2x = -4

Divide each side by '2'.
x = -2

Simplifying
x = -2

See similar equations:

| y=x(2i*3i) | | 6(x+1)/4=3x-1 | | y=4-4+2y | | 2(x+4)/4=4x-3 | | 4x+20=2x-3 | | 6x+17=-3x+35 | | 4-5n=-9+8n | | V(x)=7/3x | | 12x-4=-16x+8 | | 12x-5x+150=12x+65 | | M^2-5mn+6n^2=0 | | 15x^2-23x+3=-3 | | 9c/5=17 | | 0.06x(12000-x)(0.02)=12000 | | 7/3x | | 15.42+0.07=15.92-0.12 | | 13/7=1_/7 | | 2(6-4a)=12-8a | | -14x-19=-159 | | 5x+2x+20=90 | | 73x+13x=10+53x | | p=9+-0.5q | | y-4/3x=12 | | 7x+20=2x-5 | | x-1.5=0 | | 56X^2+35X=0 | | 2-2n=3n+15 | | -16r=192 | | 4(4x+6)+7=16x+31 | | 120=r+70-30 | | wx/y=z | | 96-X=90 |

Equations solver categories